β-Glucans in particulate and solubilized forms elicit varied immunomodulatory and apoptosis effects in teleost macrophages in a dosedependent manner - Wu, Zhelin; Yang, Yanjian; Li, Jiadong; Bossier, Peter; Wei, Xiayi; Guo, Zheng; Han, Biao; Ye, Jianmin (Frontiers in Immunology, 2023)
β-Glucans are a group of heterogeneous glucose polymers that possess immunomodulatory activities. The complex nature of their structures, uncertainty regarding the doses, and variable immune effects pose a challenge to comprehensive understanding. In this study, we investigated the immune responses and apoptosis effects in Nile tilapia (Oreochromis niloticus) head kidney macrophages (MФ) upon exposure to two β-Glucans (Paramylon and Laminarin) at low and high doses. Our results demonstrate that Paramylon elicits more robust immune responses than Laminarin, albeit with a dose-limiting effect. We also observed that the high-dose Paramylon induces apoptosis, whereas no such effect was detected in Laminarin treatment. Mechanistically, high-dose Paramylon activates the intrinsic apoptosis pathway, with significantly up-regulation of intrinsic apoptosis-related genes and impaired mitochondrial function. On the other hand, Laminarin triggers metabolic reprogramming in MФ, resulting in the enrichment of the metabolite α-Ketoglutarate, which protects the MФ from apoptosis. Overall, our findings highlight the importance of identifying the optimal dose range for β-Glucans, based on sources or structures, to achieve maximal immunomodulatory effects. These results have important implications for the design and optimization of β-Glucans-based drugs or adjuvants in immunotherapies.